KRIYA TAPESTRI DALAM OBJEK KUCING - Eria Yolanda, Dra, Minarsih, M.Sn., Drs. Erwin, M.Sn. (Serupa The Journal of Art Education, 2018)
Man likes a cat because a its looking beautiful, friendly, spoiled and friendly. However, some the people are not like it. The writer very love the animal therefore the purpose of work are to realize moment of a cat as the source of fun through step in your five steps of them; preparation, elaboration, synthesis, the realization the concept, and finishing the end terminated by held exhibition. Finally writer generate 7 work tapestri with a tittle, including: swathe color, a jungle cat, gaze plaintive, that look that the up anger, angry, character, a mixture. Recommended to collage students and citizens to be more developed technique and object tapestri work in the future.Keywords: Cat, Tapestri, and soumak geordes technique